KONSEP ACTUATING DALAM ALQURAN DAN HADITS - Wisudaningsih, Endah Tri (Humanistika : Jurnal Keislaman, 2018)
Abstract Actuating as one of the functions and also the stages of management, many mean a business move or run. In an educational institution, actuating can be interpreted to mobilize or give direction to the existing resources in the institution, whether human resources or other resources.Mobilizing human resources is a process that goes from human resource planning, recruitment, education and human resources training, and the motivation given to that resource. While mobilizing other resources is the effort to maximize the use of existing resources or move elements -element organization to perform all activities that have been planned. Keywords: Actuating,Leading, educational institution.